Effect of solvent addition sequence on lycopene extraction efficiency from membrane neutralized caustic peeled tomato waste. (15th January 2017) - Phinney, David M.; Frelka, John C.; Cooperstone, Jessica L.; Schwartz, Steven J.; Heldman, Dennis R.
Highlights: Caustic tomato peel waste can be neutralized without the use of chemical additions. Extraction efficiency ranged from 32% to 95% solely based on solvent sequence. Neutralization did not always increase extraction efficiency. Tomato fiber changed structure when exposed to acetone in a caustic environment. Abstract: Lycopene is a high value nutraceutical and its isolation from waste streams is often desirable to maximize profits. This research investigated solvent addition order and composition on lycopene extraction efficiency from a commercial tomato waste stream (pH 12.5, solids ∼5%) that was neutralized using membrane filtration. Constant volume dilution (CVD) was used to desalinate the caustic salt to neutralize the waste. Acetone, ethanol and hexane were used as direct or blended additions. Extraction efficiency was defined as the amount of lycopene extracted divided by the total lycopene in the sample. The CVD operation reduced the active alkali of the waste from 0.66 to <0.01 M and the moisture content of the pulp increased from 93% to 97% (wet basis), showing the removal of caustic salts from the waste. Extraction efficiency varied from 32.5% to 94.5%. This study demonstrates a lab scale feasibility to extract lycopene efficiently from tomato processing byproducts.